Sexual Violence Among Foreign Women Case Study - Sözen, Mehmet Şevki; Tüzün, Birgül; Fincancı, Şebnem Korur; Dokgöz, Halis (The Bulletin of Legal Medicine, 1999)
The quickly increasing number of foreign women, with various reasons, moving to Istanbul, where the socio-cultural changes are dense, is parallel to the upwards trend of sexually related violence. In this study, 32 foreign women’s autopsies performed at the Morgue Department of the Council of Forensic Medicine in 1996 are investigated. Sexual violence cases are defined, and 2 of them are presented. Multiple injuries due to blunt traumas are found in both cases which are classified in 25-35 age group. Manner of death, trauma findings, cause of death and laboratory results are examined and the reason of the deaths are thought to be of sexual violence. The results are important for emphasizing how bizzare sexual violence can be.Keywords: Foreign women, Sexual violence, Death
Keywords: foreign women; sexual violence; death